2019
DOI: 10.1080/00016489.2018.1527037
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of second primary cancers in young laryngeal carcinoma patients

Abstract: Background: Laryngeal squamous cell carcinoma (LSCC) is rare in the young. Objectives: We characterized the clinical behavior of LSCC and assessed the presentation of second primary tumors (SPCs) in this patient population. Materials and methods: Data from the Finnish Cancer Registry (FCR) were used to identify an epidemiological series of LSCC patients diagnosed at the age of 40 years or under, during 1953-2012 in Finland. Data regarding primary treatment, survival and SPCs were available. To further characte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
(51 reference statements)
0
5
0
Order By: Relevance
“…Our search criteria identified, 5540 papers and after removal of duplicates, 61 papers were selected for data review and are summarized in Table . Most of the studies were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Our search criteria identified, 5540 papers and after removal of duplicates, 61 papers were selected for data review and are summarized in Table . Most of the studies were retrospective.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, some studies proposed that common genetic factors may play a role in SPC risk in younger patients. Interestingly, regarding laryngeal carcinoma, a study by Silén et al [ 38 ] reported that SPCs in younger patients occurred at approximately the same age as in laryngeal carcinoma patients in general. However, the reason behind this remained unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Early stages usually require single modality treatment, while advanced cancers involve a combination of modalities. In recent studies conducted since 2000, some authors reported preferences for radiation [14,[62][63][64] (Table 2), while others reported a higher proportion of patients treated with surgery [15]. Accordingly, the significant heterogeneity between studies of clinical staging of young patients may cause enormous downstream variability and bias in the choice of therapeutic modalities.…”
Section: Adultsmentioning
confidence: 99%
“…Depending on the cohort features, the 5-year OS of young adults with LSCC significantly varies across studies, ranging from 55 to 87.5% (Table 2) [8,15,62,[65][66][67]. Glottic SCC seems to entail better survival outcomes than supraglottic SCC in young adults [62], but the proportion of anatomical location of tumour varies between studies (Table 2). As for clinical staging, there is an important heterogeneity between studies in the prognosis of laryngeal cancer in young versus old patients.…”
Section: Prognosismentioning
confidence: 99%
See 1 more Smart Citation